2021
DOI: 10.1002/cyto.b.21991
|View full text |Cite
|
Sign up to set email alerts
|

Validation of inducible basophil biomarkers: Time, temperature and transportation

Abstract: Background:The short stability window of several hours from blood collection to measuring basophil activation has limited the use of flow cytometry-based basophil activation assays in clinical settings. We examine if it is possible to extend this

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In the mid 1990’s the CD63 activation marker was discovered and currently is the most favored activation marker because it is directly related to histamine release and it is easily accessible since it is expressed in a distinct positive population. 48 , 76 , 78 The other valuable marker is CD203c; 79 however, it does not form a distinct positive population and is a more general basophil marker which can be used both as an identification and as an activation marker. 48 CD63 and CD203c are upregulated after IgE receptor aggregation but follow partially different metabolic pathways.…”
Section: Future Directions Of the Basophil Activation Testmentioning
confidence: 99%
“…In the mid 1990’s the CD63 activation marker was discovered and currently is the most favored activation marker because it is directly related to histamine release and it is easily accessible since it is expressed in a distinct positive population. 48 , 76 , 78 The other valuable marker is CD203c; 79 however, it does not form a distinct positive population and is a more general basophil marker which can be used both as an identification and as an activation marker. 48 CD63 and CD203c are upregulated after IgE receptor aggregation but follow partially different metabolic pathways.…”
Section: Future Directions Of the Basophil Activation Testmentioning
confidence: 99%
“…A major hurdle for implementation of the BAT into routine diagnostics is the requirement to analyze blood samples within a few hours after donation a limitation that has already been addressed by other BAT‐specialists. Their results showed that a delayed analysis of samples (after stimulation, staining, and preparation) even after 5 days of storage may be feasible if using CD63 expression as a marker for basophil activation 30,33 …”
Section: Discussionmentioning
confidence: 99%
“…Appropriately enough as we head into the holiday season, several of the articles in this issue provide ample food-for-thought. For example, Kim et al, challenge both the standard practice related to reporting BAT results as well as the current accepted specimen stability (Kim et al, 2021), while the conclusions from Göçer and Kurto glu regarding the prognostic value of hematogones in MM patients seems to be in direct contrast to their value in AML (Göçer & Kurto glu, 2021).…”
Section: Smith Et Al Present a Casementioning
confidence: 99%
“…the peritoneal fluid, to the responsiveness of innate immune cells in inflammatory bowel disease (IBD) patients, to basophil activation testing (BAT), are covered in this issue (Göçer & Kurto glu, 2021;Johansson et al, 2021;Kim et al, 2021;Spijkerman et al, 2021;Takahashi et al, 2021). Three manuscripts include an emphasis on the method validation in light of the context of use (COU) of the assay (Braudeau et al, 2021;Johansson et al, 2021;Kim et al, 2021) while others focus on the predictive value of the testing results (Göçer & Kurto glu, 2021;Spijkerman et al, 2021;Takahashi et al, 2021). The manuscript from Göçer and Kurto glu additionally highlights the impact of the cutoff values on the COU (Göçer & Kurto glu, 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation